Impact Of Corporate Social Responsibility On The Company's Reputation In Manufacturing Companies In The Basic Industry And Chemicals Sector, Cement Sub-Sector Listed On The IDX 2012-2017 - Syamsul Riyadi; Ilham Safar (ITB AAS INDONESIA, 2021)
This study uses secondary data sources via the Indonesia Stock Exchange website as a sample of manufacturing companies in the basic industrial sector and chemical sector of the cement sub-sector from 2012 to 2017. This research data was analyzed using the partial least squares (PLS) method. program. The results showed that: (1) corporate social responsibility (X1) has a significant effect on the reputation of the company (X2). (2) Corporate social responsibility (X1) has a significant effect on the value of the company (Y). (3) the reputation of the company (X2) has a significant effect on the value of the company (Y). (4) Corporate social responsibility (X1) has a significant effect on the value of the company (Y) mediated by the reputation of the company (X2).